2020
DOI: 10.3171/2018.11.jns181815
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of metabolic connectivity in a rat model of deafferentation pain: a 18F-FDG PET/CT study

Abstract: OBJECTIVERefractory deafferentation pain has been evidenced to be related to central nervous system neuroplasticity. In this study, the authors sought to explore the underlying glucose metabolic changes in the brain after brachial plexus avulsion, particularly metabolic connectivity.METHODSRats with unilateral deafferentation following brachial plexus avulsion, a pain model of deafferentation pain, were scanned by small-animal 2-deoxy-[18F]fluoro-d-glucose (18F-FDG) PET/CT to explore the changes of metabolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…The altered metabolic connectivity revealed the changes in brain functional network, which was associated with pathophysiology of disorders. Our previous study also showed that neuropathic pain following BPAI induced metabolic connectivity changes significantly among sensorimotor-related areas and pain-related area in bilateral hemispheres (Huo et al, 2020). The specific neuroplasticity pattern might provide further insights to the mechanism of neuropathic pain following BPAI.…”
Section: Discussionmentioning
confidence: 81%
“…The altered metabolic connectivity revealed the changes in brain functional network, which was associated with pathophysiology of disorders. Our previous study also showed that neuropathic pain following BPAI induced metabolic connectivity changes significantly among sensorimotor-related areas and pain-related area in bilateral hemispheres (Huo et al, 2020). The specific neuroplasticity pattern might provide further insights to the mechanism of neuropathic pain following BPAI.…”
Section: Discussionmentioning
confidence: 81%
“…Our previous study has revealed a specific pattern of brain metabolic changes following unilateral BPAI. Metabolic connectivity based on sensorimotor-related seed ROIs indicated extensive involvement of bilateral hemispheres in the development and persistence of pain, including motor cortex, somatosensory cortex, dorsolateral thalamus, and caudate putamen (16). Meanwhile, neuropathic pain would also cause plastic changes in interconnected regions instead of segregated regions alone.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of BPAI has been described in our previous articles (14)(15)(16). Briefly, the rats were anesthetized using sodium Abbreviations: 18 pentobarbital with an intraperitoneal injection (40 mg/kg), then placed on a thermostatic operating table.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Flor et al reported that neuropathic pain due to amputation was related to expansion of the adjacent region, 12,50 which was consistent with our previous research. 19,51 Studies also revealed that cortical changes were not restricted to the sensorimotor cortex, but also an involved extensive range of areas, including the thalamus, anterior insula, and others. [52][53][54] The thalamus is the main relay of sensory and spinal nerve pathways (spinothalamic tract), which is important for the development of deafferentation pain.…”
Section: Discussionmentioning
confidence: 99%